Evaluation of selected Chinese cassia (Cinnamomum cassia Blume) accessions for chemical quality - REMA, P A MATHEW, B KRISHNAMOORTHY, T JOHN ZACHARIAH, J (Journal of Spices and Aromatic Crops, 1999)
Twenty five Chinese cassia (Cinnamomum cassia) accessions were analysed at 15% moisture level for bark oil, bark oleoresin and leaf oil percentages. Bark oil ranged from 1.2 to 4.9%, leaf oil 0.4 to 1.6% and bark oleoresin 6.0 to 10.5%. Cinnamaldehyde was the major constituent in both leaf and bark oils. Accessions A, and C, had high bark oleoresin and D" D3 and D, high bark oil and cinnamaldehyde contents.